Kekuatan Statik Rangka Mesin Alat Penyortir Barang Menggunakan Software Solidworks - Abdul Muchlis; Achmad Risa Harfit (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The use of automation systems is needed in sorting, one of which is the sorting of objects based on the size of the object being sorted. Especially in the sorting process, there are still many industries that use conveyors that only function for one product with the same weight characteristics. Therefore, to sort the same goods with different weights, a separate conveyor is needed so that many conveyors are used. The development of a sorting machine is an important aspect in the modern automation and manufacturing industry. This research aims to design and analyze the static loading of the sorting machine frame using SOLIDWORKS software. The design method used includes detailed 3D modeling of the machine frame by considering the strength, stability and reliability of the structure. The simulation results using SOLIDWORKS software show the stress (von Mises) with a maximum value of 82.26 MPa, while the theoretical calculation result is 84 MPa. Displacement with a maximum value of 4.063 mm, while the theoretical calculation result is 1.60 mm. The safety factor is 2.38, while the theoretical calculation result is 2.43. The difference between manual calculation and simulation is 0.02% for von Mises stress, 1.5% for displacement, and 0.02% for safety factor.